“He told me my pain was in my head”: mitigating testimonial injustice through peer support - Vigouroux, Marie; Newman, Gillian; Amja, Kristina; Hovey, Richard Bruce (Frontiers in Pain Research, 2023)
Introduction Women with disabilities are exposed to sexism and ableism, earn less income, and work in exceptionally challenging conditions compared to women without disabilities and men with or without disabilities. Adolescent girls living with scoliosis may begin experiencing this compounding bias during their encounters with healthcare from the moment they start noticing differences in their bodies. Being significantly more likely than boys to progress to a curve angle where painful treatment such as bracing or spinal fusion surgery is required, adolescent girls living with scoliosis are therefore more likely to experience chronic pain. The long-term impact of pain and pain-related stigma includes lower educational attainments, decreased vocational functionality, and social impairments in adults after having experienced chronic pain in adolescence. Approach In this article, the authors will explore the effects and mechanisms of gender-specific peer support in disrupting this trajectory to adverse outcomes. Through individual interviews consisting of open-ended questions, the researchers gathered narrative data from Curvy Girls members, a community-based peer support group for girls and young women living with scoliosis. The data was analyzed using an applied philosophical hermeneutics approach, with intersectionality and testimonial injustice as their framework. Findings They found that the study participants had their pain narratives reinterpreted by the adults in their lives, including their parents and healthcare practitioners, leading them to question and doubt their own experiences. Discussion These negative outcomes were mitigated through the peer support they received and offered from Curvy Girls. Participants reported having gained confidence and a sense of belonging after they joined this group, allowing them to better cope with their condition more effectively in different facets of their lives.